2008
DOI: 10.1080/13504850600748968
|View full text |Cite
|
Sign up to set email alerts
|

The Shapley decomposition for portfolio risk

Abstract: The aim of this article is to provide an application of the Shapley value to decompose financial portfolio risk. Decomposing the sample covariance risk measure, gives us relative measures, which can be, classified securities of a portfolio according to risk scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…This is because the process of portfolio formation can be interpreted as a cooperative game where the assets are the players that form coalitions to reduce risk (see Kadan, ; Colini‐Baldeschi et al, ). Consequently, the corresponding Shapley values of the assets reflect their contribution to the overall portfolio risk (see Mussard and Terraza, ) . They consider all possible asset coalitions and by averaging their marginal effects obtain a multidimensional contribution.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the process of portfolio formation can be interpreted as a cooperative game where the assets are the players that form coalitions to reduce risk (see Kadan, ; Colini‐Baldeschi et al, ). Consequently, the corresponding Shapley values of the assets reflect their contribution to the overall portfolio risk (see Mussard and Terraza, ) . They consider all possible asset coalitions and by averaging their marginal effects obtain a multidimensional contribution.…”
Section: Introductionmentioning
confidence: 99%
“…A non-exhaustive list of recent applications include Israeli[9], Mussard and Terraza[14], and Sastre and Trannoy[16].…”
mentioning
confidence: 99%
“…Some authors have suggested that the use of SHAP values is the only explainable AI approach that has been established in an economic field (Bussmann et al, 2021 ). Shapley-based XAI models have been used in many research studies in the field of finance (Mussard and Terraza, 2008 ; Ariza-Garzón et al, 2020 ; Bussmann et al, 2020 ; Giudici and Raffinetti, 2020 ).…”
Section: Artificial Intelligencementioning
confidence: 99%